First, use this rule of exponents to rewrite the expression and cancel common terms:
#a = a^color(blue)(1)#
#((x^7y^5)/(xy^5))^2 => ((x^7y^5)/(x^color(blue)(1)y^5))^2 => ((x^7color(red)(cancel(color(black)(y^5))))/(x^color(blue)(1)color(red)(cancel(color(black)(y^5)))))^2 => (x^7/x^color(blue)(1))^2#
Next, use this rule of exponents to simplify the term within the parenthesis:
#x^color(red)(a)/x^color(blue)(b) = x^(color(red)(a)-color(blue)(b))#
#(x^color(red)(7)/x^color(blue)(1))^2 => (x^(color(red)(7)-color(blue)(1)))^2 => (x^6)^2#
Now, use this rule of exponents to complete the simplification:
#(x^color(red)(a))^color(blue)(b) = x^(color(red)(a) xx color(blue)(b))#
#(x^color(red)(6))^color(blue)(2) => x^(color(red)(6) xx color(blue)(2)) => x^12#